Breast feeding twins and high multiples. Issue 5 (21st August 2006) - Flidel-Rimon, O; Shinwell, E S
Abstract : Breast feeding offers major health advantages for all infants, whether born singleton or from multiple pregnancy. Adequate quantity and quality of milk production has been documented even for high multiples. Combined efforts of parents, close family, friends, and the medical team can help to make either full or partial breast feeding of multiples possible.